Addressing Climate Change in the Middle East and North Africa (MENA) - Cervigni, Raffaello; Pariente-David, Silvia; Rigaud, Kanta K.; Holten, Johanne; Coma Cunill, Roger (World Bank, Washington, DC, 2012)
The brief includes the following headings: Middle East and North Africa (MENA) vulnerability to climate change; World Bank program - overall approach; reducing vulnerability; carbon emissions and low carbon growth; promoting low-carbon growth; and region-wide activities.